Natural Chinese herbs for the prevention and treatment of acute pancreatitis: a narrative review - Jiaqi Cui; Di Wu; Huimin Zhou; Haiyan Chen; Zhixia Dong; Jun Yang (Journal of Pancreatology, 2022)
Acute pancreatitis (AP) is a disease characterized by local inflammation in the pancreas, followed by trypsin activation, and may result from multiple etiologies. Approximately 20% of AP can progress to severe acute pancreatitis (SAP), which can lead to systemic inflammatory response syndrome (SIRS) and multiple organ dysfunction syndromes (MODS). SAP mortality rates have remained high in recent years, but there are currently no specific drugs designed to reduce these rates. Clinical studies have shown that patients can reduce the symptoms of the disease and slow down the development of the disease after taking the Chinese medicine decoction. Basic studies have shown that in AP or SAP disease models, the use of Chinese medicine monomers can improve the condition of rates. These natural Chinese herbal products can improve pancreatitis, given their ability to act on multiple targets. However, they have not been widely employed clinically and studied sufficiently and thoroughly. Therefore, this review aimed to summarize the pathophysiological mechanisms underlying pancreatitis and review the potential role of natural Chinese herbs (monomers and decoctions) in clinical and basic research.